Transformasi Pemikiran Syed Muhammad Naquib Al-Attas pada Komunitas Institute for the Study of Islamic Thought and Civilizations (INSISTS) di Indonesia - Yanuardi Syukur (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2019)
The transformation of intellectual thought from Malaysia, Syed Al-Attas in Indonesia, was carried out massively by young intellectuals who were members of the Institute for the Study of Islamic Thought and Civilization (INSISTS) who had been students of Al-Attas in Kuala Lumpur, Malaysia. In the transformation of this point of view, the INSISTS Community became a controlling actor (act) in controlling the network of the spread of Al-Attas ideas which was carried out using technology in a network based on the similarity of ideas and thoughts. The role of INSISTS as an actor in this transformation makes this community an act in terms of the transformation of Al-Attas thinking in Indonesia.